Platelet-Rich Fibrin Matrix (PRFM) for Androgenetic Alopecia - Sclafani, Anthony P. (Facial Plastic Surgery, 2014)
The objective of this study was to determine the effect of platelet-rich fibrin matrix (PRFM) treatment on androgenetic alopecia. Prospective cohort study of 15 (9 male and 6 female) subjects with androgenetic alopecia for at least 1 year who were treated with intradermal injections of autologous PRFM three times on a monthly basis. Hair density indices were measured in triplicate in the same area of the scalp before the treatment and 1, 2, 3 and 6 months after initial treatment. Hair density index (HDI) measurements were obtained and compared with pretreatment values for each subject. After a series of three intradermal PRFM injections, hair density indices increased significantly at 2 (47.4 ± 22.7%, p = 0.0031) and 3 (106.4 ± 56.9%, p = 0.0277, paired t-test) months after the initial treatment, and approached statistical significance at 6 months (75.1 ± 46.82%, p = 0.0606) after the initial treatment. Patients who achieved greater than 25% increase in HDI by 2 months after the initial treatment were more likely to have greater than 25% improvement at 6 months after the initial treatment (100 vs. 16.7%, p = 0.0476). Androgenetic alopecia affects a significant number of both men and women. A series of intradermal injections of autologous PRFM increased the HDI in patients with androgenetic alopecia at 2 and 3 months after initial treatment; this improvement approached statistical significance at 6 months after initiating treatment. Autologous PRFM injections may be a valuable treatment for androgenetic alopecia, particularly in cases with mild hair loss. The level of evidence is level 2.
Keywords: platelet-rich fibrin matrix; platelet-rich plasma; growth factors; alopecia; hair restoration